Information management in smart grids: Who should govern information management to balance between coordination and competition on the distribution grid level? - Marius Buchmann (Jacobs University Bremen, Bremen Energy Research (BER), 2016)
Smart grids should increase coordination on the distribution grid level and facilitate new market opportunities (I.e. competition on a level playing field). Information management is becoming a new task in the electricity supply chain. It is an enbaler for the development of smart grids. Therefore, the governance of information management should as well efficiently balance between coordination and competition. Within this paper we analyse which role from the energy sector could govern the information management system. We conclude that neither of identified roles within the energy sector governing information management could secure both coordination and competition, at the same time. Therefore, new governance approaches (or new roles) are required.
Keywords: 330; Smart Grid; Information Management; Governance; Coordination